PENGGUNAAN TEPUNG IKAN SAPU-SAPU (Pterygoplichthys pardalis) SEBAGAI SUMBER PROTEIN PAKAN PADA PENTOKOLAN UDANG VANAME (Litopenaeus vannamei) - Hasnidar Hasnidar; Andi Tamsil; Muhammad Saenong; Andi Muhammad Akram; Muh . Ardiansyah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
Vannamei shrimp (Litopenaeus vannamei) is a fishery product that is able to generate foreign exchange for the country besides tiger prawns. This shrimp has the advantage of being more resistant to environmental conditions and disease. Feed plays an important role in its cultivation because it absorbs the largest cost of 60-70% of the total production cost. At present, there are still many farmers, both traditional and modern, who have not carried out effective feeding because of the high cost of providing feed. Amazon sailfin catfish, Pterygoplichthys pardalis are invasive fish in waters that need to be limited in population development by using them. One form of utilization is to make it a fish meal product and then it becomes a raw material for feed. This study aims to analyze the use of P. pardalis meal as feed for vaname shrimp. The test animals were vaname shrimp with a weight of 3.35±0.5 g; total length 6±0.5 cm, first acclimatized for 5 days. The percentages of using broomstick fish meal were 25%, 30%, 35% as treatment and commercial feed as control feed. The study used a completely randomized design (CRD) with 4 treatments and 3 replications. Research for 60 days, the dose of feed given is 5% with a frequency of 5 times a day. The parameters observed were: absolute growth (PM), daily growth (PH), daily growth rate (LPH), feed conversion (KP), feed efficiency (EF) and survival (KH). Data were analyzed for variance (ANOVA). The results showed that the higher the percentage of P. pardalis meal, the better the response of vannamei shrimp to growth parameters, but based on the analysis of variance, it showed that the treatment not significant all the parameters observed.